MnO2/MXene–Ti3C2Tx flexible foam for use in lithium ion storage. Issue 14 (23rd June 2021) - Yan, Jingze; Yu, Lu; Wang, Donghua; Zhang, Wenyuan; Xiong, Zhihao; Nie, Tianshuo; Ji, Zhen; Yan, Xiaoqin
Abstract : As a new two-dimensional material, MXene has attracted extensive attention because of its unique structure and electrochemical properties. Abstract : As a new two-dimensional material, MXene has attracted extensive attention because of its unique structure and electrochemical properties. MXene-based self-supporting films have been widely studied due to their flexibility, light weight and lack of need for adhesives and conductive agents. In the present work, we used facile ultrasonic and annealing methods to fabricate MnO2 /MXene–Ti3 C2 T x foam hybrids for lithium storage. In the hybrid material, MnO2 nanoparticles expand the MXene lamellar spacing, provide tunnels for lithium ion shuttling and accelerate the transport speed of lithium ions, thus improving the rate performance of the electrode materials. The existence of the MXene nanosheets can release the internal stress due to the volume expansion of MnO2 during charging/discharging, reduce the electrode resistivity and improve the cycling stability of materials. The initial discharge capacity can reach 1203 mA h g −1 and the capacity can be maintained at about 600 mA h g −1 after 200 cycles. Moreover, the capacity of the electrode attenuates less at a large current and the capacity is about 350 mA h g −1 at 5 A g −1 .